Neuroscience Outside the Box: From the Laboratory to Discussing Drug Abuse at Schools - Machado do Vale, Thereza Cristina; da Silva Chagas, Luana; de Souza Pereira, Helena; Giestal-de-Araujo, Elizabeth; Arévalo, Analía; Oliveira-Silva Bomfim, Priscilla (Frontiers in Human Neuroscience, 2022)
One of the effects of the current covid-19 pandemic is that low-income countries were pushed further into extreme poverty, exacerbating social inequalities and increasing susceptibility to drug use/abuse in people of all ages. The risks of drug abuse may not be fully understood by all members of society, partly because of the taboo nature of the subject, and partly because of the considerable gap between scientific production/understanding and communication of such knowledge to the public at large. Drug use is a major challenge to social development, and a leading cause of school dropout rates worldwide. Some public policies adopted in several countries in recent decades failed to prevent drug use, especially because they focused on imposing combative or coercive measures, investing little or nothing in education and prevention. Here we shed light on different approaches to combating drug use, and highlight the role of neuroscience education as a preventive approach, showing examples of recent successful efforts. We propose building a bridge between schools and scientists by creating programs that promote information, student engagement and honest dialogue, and show evidence that public policy regulators should be persuaded to support such science-based education programs in their efforts to effect important positive changes in society.